The Relationship Between Trading Volume and Market Returns: A VAR/Granger Causality Testing Approach in the Context of Saudi Arabia - Alhussayen, Hanan (Organizations and Markets in Emerging Economies, 2022)
This paper investigates the relationship between trading volume and market returns in the Saudi stock market. Daily data of number of shares traded and TASI returns from 2010 till mid-2021 are used for the same. The Granger causality test reveals a unidirectional relationship from returns to volume. This is supported by the findings of the VAR test and the Impulse Response Function (IRF) test. Trading volume does not carry informational content and cannot predict prices. Returns do impact volume, but the effect is not steady. The results do not provide support for the Sequential Information Arrival Hypothesis (SIAH). The asymmetric information model and the difference of opinion model can provide an explanation for the obtained results.
Keywords: trading volume; market returns; Sequential Information Arrival Hypothesis (SIAH); VAR; Granger causality